If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + -2x = 81 + x Solving 60 + -2x = 81 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 60 + -2x + -1x = 81 + x + -1x Combine like terms: -2x + -1x = -3x 60 + -3x = 81 + x + -1x Combine like terms: x + -1x = 0 60 + -3x = 81 + 0 60 + -3x = 81 Add '-60' to each side of the equation. 60 + -60 + -3x = 81 + -60 Combine like terms: 60 + -60 = 0 0 + -3x = 81 + -60 -3x = 81 + -60 Combine like terms: 81 + -60 = 21 -3x = 21 Divide each side by '-3'. x = -7 Simplifying x = -7
| 25x^2y^4+10xy^3-15x^2y^5=0 | | 6x^2+15x-7=0 | | f=1/2(hp) | | 7t-16=-51+2t | | 0.75x^2+1.5x-150=0 | | 3-2x^2-8=0 | | 0.3n=-12 | | 4+3x-0.5x^3=0 | | In(e^3)=In(e^3)+In(e^5) | | 8(2q-2)= | | 2(w^2-36)=0 | | 8x+4z=5+7y | | f(x)=3x^2+6x-4 | | 3e^2x=44 | | ln(x^5/x^4) | | 3x^2-5x+x^2-5x=x | | m=2/3.(7.-9) | | 3x^4-2x^3+22x^2-18x-45=0 | | -8=4+0.125b | | 2b^2+17b+35=0 | | 5(8y-9)-(7y+6)= | | 5y/y^2-2y | | 2cos(6x)+1=0 | | 4p-24=-4+8p | | 5y/y*2-2y | | 3m-20=-34+m | | 317g=kg | | 103x-4=-215x+632 | | x*x+10x=39 | | 3t*6p*5t= | | 2x+3y+2-y-8x-7= | | m+3m+5m-9= |